Perceptions of poverty and the perpetuation of the capability-judgment cycle in outer southeast Melbourne. Issue 5 (19th October 2016) - Kelly, Leanne M.
Abstract: People living in poverty are subject to assumptions and stereotypes which, whether inaccurate, harmful, or misguided, can impact empowerment and capability building. This research explores perceptions relating specifically to people in poverty in outer southeast Melbourne suburbs. Perceptions of 218 non-poor respondents are compared with the perceptions of 52 poor respondents. Poor respondents describe themselves before discussing impacts of negative non-poor perceptions. Findings demonstrate that the non-poor tend to view the poor negatively and that these judgments have adverse impacts on those in poverty. Non-poor perceptions in this study are shown to influence the perpetuation of poverty by contributing to a cause and effect capability-judgment cycle. This cycle illustrates how non-poor views impact emotional and material wellbeing of the poor and influence policy, programs, and poverty discourse in ways which further reduce the capabilities of the poor to achieve valued ends.